Optical, magnetic characterization, and gamma-ray interactions for borate glasses using XCOM program - Y. S. Rammah; A. S. Abouhaswa; A. H. Salama; R. El-Mallawany (Journal of Theoretical and Applied Physics)
Abstract In the present study, the optical characterization of borate glasses with composition 35Li2O − 10ZnO − 55B2O3 − xMnO2: x = 0, 0.5, 1.0, 1.5, and 2.0 wt% has been investigated. The absorption spectra measurements within the wavelength domain 200–1000 nm have been carried out. The optical energy gap of the investigated samples using the absorption spectrum fitting (ASF) model has been calculated. The molar refraction, molar polarizability, reflection loss, optical transmission for the samples were estimated. The metallization criterion, dielectric constant, refractive index, and energy band metallization criterion for the studied glasses were estimated. Magnetic property measurements for all glass samples were carried out at 300 K. Additionally, the prospects of gamma-ray interactions with the investigated glasses have been achieved through studying the total mass attenuation, coherent, Compton, photoelectric, and pair production interactions at photon energy in the range of 0.356–1.330 MeV. Results reveal that the optical and magnetic properties of the investigated glasses change with changing the MnO2 concentration. Studied glasses can be used as a candidate for optical fiber and optical devices application. In the other hand, at lower gamma photon energy range, the photoelectric absorption dominates with the glasses, while as the energy increases, the probability of Compton scattering and pair production become the most dominate interactions.